Development Of History Interactive Learning Media Through Ludo Teaching To Improve Student's Critical Thinking - Aisyah Nur Hanifah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The teaching and learning process is a communication process that undergoes and changes to develop an interactive-based learning model, with the use of learning media being part of learning resources which is a combination of software (learning materials) and hardware (learning tools). Media can foster positive attitudes in students and transform the role of teachers in a more positive and productive direction. According to Reigeluth (1999), in supporting the learning process there are three learning variables, namely variables of learning conditions, methods, and variables of learning outcomes. Knowledge in historical teaching materials to Vocational Middle School Students, a teacher not only teaches theory but also through practice, like playing Ludo games. By learning to use game teaching, ludo in history learning can be a capital for teachers to act as an evaluation stage in measuring students' ability to be able to improve their thinking power through HOTS questions. The need to increase critical thinking in students, because of the enormous influence of critical thinking in improving student learning so that the results are good and following what is expected by teachers in schools. Bayer (1995), “Reasonable critical thinking.” Critical thinking is useful for studying the validity of the form (statements, ideas, arguments, research, etc.).